Preference of Atta capiguara (Hymenoptera, Formicidae) for Different Grasses - Vitorio, Alberto C.; Forti, Luiz C. [UNESP]; Rodella, Roberto A. [UNESP]; Costa, Ciniro [UNESP]; Caldato, Nadia [UNESP]; Fujihara, Ricardo T. [UNESP]; Silva, Marcilio S. [UNESP] (California State University, 2011)
The preference of Atta capiguara for young leaves was evaluated and developed for nine grass species. Hyparrhenia rufa, Paspalum notatum cv Comum and Andopogon gayanus were the most preferred. Paspalum notatum cv Pensacola, Brachiaria decumbens and Cynodon dactylon cv Coast Cross presented intermediate preference. Brachiaria brizantha, Brachiaria humidicola and Melinis minutiflora stood out as the least preferred. In general, H rufa was the most consumed species independent of leaf age. The proportions of crude protein, ethereal extract, calcium, phosphorus, cellulose, lignin and silica extract of grass species did not present any relation with preference by Atta capiguara Goncalve. Grass species less accepted by A. capiguara can guide pasture management and on the other hand, preferred species can aid in the formulation of toxic baits more attractive to this species of leaf-cutting ant.
Keywords: leaf-cutting ants; plant selection; pasture